Crystal structure of betaine aldehyde dehydrogenase from Burkholderia pseudomallei. Issue 2 (28th January 2022) - Beard, Dylan K.; Subramanian, Sandhya; Abendroth, Jan; Dranow, David M.; Edwards, Thomas E.; Myler, Peter J.; Asojo, Oluwatoyin A.
Abstract : High‐resolution apo and cofactor‐bound structures of betaine aldehyde dehydrogenase from Burkholderia pseudomallei are described. Abstract : Burkholderia pseudomallei infection causes melioidosis, which is often fatal if untreated. There is a need to develop new and more effective treatments for melioidosis. This study reports apo and cofactor‐bound crystal structures of the potential drug target betaine aldehyde dehydrogenase (BADH) from B. pseudomallei . A structural comparison identified similarities to BADH from Pseudomonas aeruginosa which is inhibited by the drug disulfiram. This preliminary analysis could facilitate drug‐repurposing studies for B. pseudomallei .